Invert classroom method for gerontogeriatric training in Medicine students - Juan Carlos Baster Moro; Luis Aníbal Alonso Betancourt; Silvia María Pérez Pérez (Medisur)
Background: the inverted classroom is a blended learning modality, where students learn the concepts by themselves, usually using educational videos, audio files and other technologies, through collaboration among peers in online communities. Objective: to propose an inverted classroom method for gerontogeriatric training in Medicine students. Methods: a cross-sectional observational study was carried out using scientific methods: document review, direct observation in the field, analysis, synthesis, induction, deduction, systemic and descriptive statistics. Results: an inverted classroom method is provided for the gerontogeriatric training of Medicine students that combines face-to-face and virtual modalities from the interaction between the forms of organization of medical teaching and education at work in the Primary Health Care: consultation and home field visit. Conclusions: the inverted classroom is a context that favors the gerontogeriatric training of the Medicine student since it revitalizes and transforms the traditional conceptions and approaches of teaching-learning, by achieving a greater student role, increased autonomy, instantaneous, interconnection, multimedia and the creativity and innovation of the student in the solution of health problems of the elderly, as well as the use of the resources and virtual learning environments’ potential that it possesses, combining face-to-face and virtual teaching modalities.